Pengaruh Akuntabilitas, Transparansi Terhadap Pengelolaan Alokasi Dana Desa Dalam Mewujudkan Good Governance (Studi Empiris Di Desa Saneo) - Novita; Baiq Kisnawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2026)
This study aims to examine the influence of accountability and transparency on the management of village fund allocations in realising good governance in Saneo village. This research is quantitative with an associative approach. The sampling technique used was saturated sampling because all village staff in Saneo village were used as samples due to its relatively small population of 44 people. The data used were primary data, collected through interviews and questionnaires. Data analysis used the Statistical Package for the Social Sciences (SPSS) version 27. The data analysis technique used was multiple linear regression. The results of this study indicate that accountability has a significant effect on the management of village fund allocations in realising good governance. Meanwhile, transparency does not have a significant effect on the management of village fund allocations in realising good governance.